Flowsheet processing secure voice traffic using incoherent reception - Антонов, Веніамін Валерійович (Ukrainian Information Security Research Journal, 2013)
The paper raised and resolved problems related to the creation and performance evaluation procedures vokal incoherent acceptance speech signals in terms of various destabilizing factors. An analytical study proved the applicability of narrowband communication systems incoherent CHFM modem diat does not require using devices of phase synchronization at the same time provides the necessary for normal functioning vocoder speed and quality transmission of voice traffic. Improved technological protection scheme parameter passing vokal voice information through a standard aircraft radio. Process improvement is die replacement of coherent transmission system vokal incoherent speech signals modem connection, which does not permit use of phase synchronization of devices and eliminates die cause of instability in die organization of sessions. As an integral element vokoder’s technology applied procedures incoherent reception vokal speech signals.